2007
DOI: 10.1016/j.gca.2007.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Linking lithology and land use to sources of dissolved and particulate organic matter in headwaters of a temperate, passive-margin river system

Abstract: A number of rivers have been found to transport highly aged organic matter [OM]; however, the sources of this aged material remain a matter of debate. One potential source may be erosion and weathering of headwater lithologies rich in ancient sedimentary OM. In this study, waters, suspended particulates, streambed sediments, rocks and soils from fourteen small headwater watersheds of a mid-size, temperate, passive margin river were sampled and characterized by D 14 C, d 13 C, and POC/TPN ratios to identify sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 67 publications
8
69
2
1
Order By: Relevance
“…These sediments presented OC characteristics ( 14 C, δ 13 C) that matched those of deeper soil layers (i.e. >30 cm) of the drainage area in the subcatchment, an observation that is in agreement with other studies that report transport of old OC in rivers when the dominant erosion processes deliver material from deeper soil layers and bedrock in the source areas into river channels (Gómez et al, 2010;Longworth et al, 2007;Masiello and Druffel, 2001). …”
Section: Old Oc Sourcessupporting
confidence: 91%
See 1 more Smart Citation
“…These sediments presented OC characteristics ( 14 C, δ 13 C) that matched those of deeper soil layers (i.e. >30 cm) of the drainage area in the subcatchment, an observation that is in agreement with other studies that report transport of old OC in rivers when the dominant erosion processes deliver material from deeper soil layers and bedrock in the source areas into river channels (Gómez et al, 2010;Longworth et al, 2007;Masiello and Druffel, 2001). …”
Section: Old Oc Sourcessupporting
confidence: 91%
“…The occurrence of erosion processes that transport deep soil in C51 was related to land use change and lithology, both of which can greatly influence the characteristics of the mobilized OC in catchments (Longworth et al, 2007). Lithology, a key component in sediment delivery (de Vente et al, 2011;Haregeweyn et al, 2006) was sensitive to the formation of gullies and mass movements in the slope-streambed connection of C51.…”
Section: Old Oc Sourcesmentioning
confidence: 99%
“…However, the d 13 C POC values for both wetlands were more depleted (231.8% 6 1.6%; Table 1) than typical for sedimentary rocks (229.3% 6 0.6%, Petsch 2000; Table 2), as well as soils and surface sediments (228.8% 6 0.7%; Table 2, Longworth et al 2007) that might be supplied from the upper HRE. Moreover, the d 13 C POC was even more depleted than that of bed sediments within the wetlands (227.0% 6 1.5%; Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…These soils have been shown to be rich in charcoal (Skjemstad et al 2002), leading us to conclude that lignite is much less than 3.8% of the riverine POM. Longworth et al (2007) observed young dissolved organic matter (DOM) in watersheds draining OM-rich shale, suggesting little or no contribution of shale organic carbon to riverine DOM. Assuming that contributions of lignite black carbon to the DOM pool are also negligible in the lower Brazos River, we conclude that lignite decomposition has a trivial impact on 14 C content of riverine DIC.…”
Section: Algal Growthmentioning
confidence: 99%